P-OGC30 High volume oesophagogastric resection in a small private hospital during COVID 19, April 2020- April 2021. (16th December 2021) - Knight, William; Theophilidou, Elena; Hossain, Tanvir; Hatt, Jake; Yanni, Fady; Zanotti, Daniela; Catton, James; Welch, Neil; Vohra, Ravi; Parsons, Simon
Abstract: Background: Like other hospitals at the peak of the pandemic, our institution had limited elective critical care capacity. This study summarises the outcomes of patients undergoing oesophagogastric (OG) resection at our institution, treated as the result of the emergency national contract between the NHS and the independent sector hospitals. Methods: Patients undergoing OG resection at our institution between April 2020 and April 2021 were included. Patients were managed through the multidisciplinary team and were treated according to standard ERAS pathways, involving critical care input. National OG Cancer Audit (NOGCA) metrics were collected and compared to pre-COVID data. Results: 81 patients underwent oesophagogastric resection in the private sector (60 oesophagectomies). Median length of stay was 9 days (9 pre-COVID). This included 21 patients who were repatriated to our main centre for ongoing management. 30-day mortality was 3.7% (1.8% pre-COVID), 90-day mortality 6.7% (4.2% pre-COVID). This included one patient who contracted COVID following discharge. 9 patients suffered an anastomotic leak, equating to a leak rate of 11% (7% pre-COVID). 22 resections were performed at our main centre (110-140 OG resection pre-COVID) Conclusions: It is likely the private institution in this study represented one of the busiest oesophagogastric centres in the UK during COVID-19. A large cohort of patients underwent potentially curative surgery as a result of the emergency contract, who would have otherwise been placed on prolonged or palliative chemotherapy. 30 and 90-day mortality and anastomotic leak rates were higher than pre-pandemic levels, reinforcing the value of centralised tertiary OG resection services.